NIR-absorbing Ru(II) Complexes Containing α-Oligothiophenes for Applications in Photodynamic Therapy - Lifshits, Liubov M. (Chembiochem, 2020)
The design of near-infrared (NIR)-active photosensitizers (PSs) for light-based cancer treatments such as photodynamic therapy (PDT) has been a challenge. While several NIR-Ru(II) scaffolds have been reported, this approach has not been proven in cells. This is the first report of NIR-Ru(II) PSs that are phototoxic to cancer cells, including highly pigmented B16F10 melanoma cells. The PS family incorporated a bis(1,8-naphthyridine)-based ligand (tpbn), a bidentate thiophene-based ligand (nT; n=0–4), and a monodentate 4-picoline ligand (4-pic). All compounds absorbed light >800 nm with maxima near 730 nm. Transient absorption (TA) measurements indicated that n≥4 thiophene rings (4T) positioned the PDT-active triplet intraligand charge transfer ((3)ILCT) excited state in energetic proximity to the lowest lying triplet metal-to-ligand charge transfer ((3)MLCT). 4T had low micromolar phototoxicity with PI(vis) and PI(733nm) values as large as 90 and 12, respectively. Spectroscopic studies suggested that the long-lived (T(TA)=3–6 μs) (3)ILCT was accessible from the (3)MLCT state, but energetically uphill in the overall photophysics. The study highlights that phototoxic effects can be achieved with NIR-absorbing Ru(II) PSs as long as the reactive (3)ILCT states are energetically accessible from the low-energy (3)MLCT states. It also demonstrates that tissue-penetrating NIR light can be used to activate the PSs in highly pigmented cells where melanin attenuates shorter wavelengths of light.